2007
DOI: 10.1097/mpg.0b013e31802c695e
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific Responses to Zinc Supplementation in Nouna, Burkina Faso

Abstract: Zinc supplementation had positive, nil, or negative effects depending on pathological condition, and the effects were different for boys than for girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Some studies have reported positive effect of zinc supplementation on weight gain [6,[29][30][31][32] but some others have not [33][34][35][36][37]. Although some studies have shown different responses from girls and boys to weight gain due to zinc supplementation, but this issue should be supported by further studies [38]. Height increment was more prominent in boys than girls so that the mean of total height increment in PG and ZG for girls were 8.28 and 9.64 cm (P=0.02), respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported positive effect of zinc supplementation on weight gain [6,[29][30][31][32] but some others have not [33][34][35][36][37]. Although some studies have shown different responses from girls and boys to weight gain due to zinc supplementation, but this issue should be supported by further studies [38]. Height increment was more prominent in boys than girls so that the mean of total height increment in PG and ZG for girls were 8.28 and 9.64 cm (P=0.02), respectively.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study from our group has shown that zinc supplementation combined with glutamine and vitamin A benefit shantytown girls at risk for enteric infections in the verbal learning testing [58]. Another study elsewhere has shown that girls suffering from diarrhea recovered faster than boys after zinc supplementation [59]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies showed that girls are less responsive than boys to zinc therapy for a number of acute infections, not just diarrhea (89). There is also some evidence that certain etiologies for diarrhea might not be zinc responsive, eg, Escherichia coli and rotavirus (90).…”
Section: Zinc Nutritionmentioning
confidence: 99%